2
$\begingroup$

In Kruger's note, the process of deriving TVC is expressed as:
$0=lim_{t \rightarrow \infty} \beta^t U'(f(k_t)-k_{t+1})k_{t+1}=lim_{t \rightarrow \infty} \beta^{t-1} U'(f(k_{t-1})-k_{t})k_{t} =lim_{t \rightarrow \infty} \beta^{t-1}\beta U'(f(k_{t})-k_{t+1})f'(k_t)k_{t}=lim_{t \rightarrow \infty} \beta^{t} U'(f(k_{t})-k_{t+1})f'(k_t)k_{t}$
The third equation is from Euler equation.
But how can I derive from first the second equation?
$lim_{t \rightarrow \infty} \beta^t U'(f(k_t)-k_{t+1})k_{t+1}=lim_{t \rightarrow \infty} \beta^{t-1} U'(f(k_{t-1})-k_{t})k_{t}$

$\endgroup$

1 Answer 1

2
$\begingroup$

But how can I derive from first the second equation? $lim_{t \rightarrow \infty} \beta^t U'(f(k_t)-k_{t+1})k_{t+1}=lim_{t \rightarrow \infty} \beta^{t-1} U'(f(k_{t-1})-k_{t})k_{t}$

You can notice that the second side of the equation is just a relabeling of the first side, where $t$ is replaced by $t-1$, so that they actually are the same equation.

In the second side of the equation we have $lim_{t \rightarrow \infty}$, even if, re-labeling, one could think that it should be $lim_{(t-1) \rightarrow \infty}$. But it is the same, as $(t-1) \rightarrow \infty \Leftrightarrow t \rightarrow \infty$ ($-1$ is a fixed number, so $t$ must go to infinity).

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.